Good corporate governance, ethnic CEO and audit fees for manufacturing companies listed on the Indonesia stock exchange (IDX) - Umi Kalsum; Luk Luk Fuadah; Rika Henda Safitri (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2021)
This study aims to examine the effect of Good Corporate Governance, CEO ethnicity, and Audit Fees in Manufacturing Companies listed on Indonesia Stock Exchange within the period of 2014-2018. The independent variable used in this study is Good Corporate Governance, which is represented by the variable of the Independent Commissioner, Audit Committee, Managerial Ownership, Institutional Ownership and CEO Ethnicity, while the dependent variable used is Audit Fee. This quantitative research employed the descriptive research method. The population in this study included manufacturing companies listed on the Indonesia Stock Exchange (IDX). The sampling technique used in this research is purposive sampling with certain criteria and 220 data were obtained from observations within the period of 2014-2018. The data were analyzed using multiple regression analysis with Statistical Package for the Social Sciences (SPSS) software by performing calculations and descriptive statistical tests, classical assumption tests, partial tests and determination coefficient tests.The results of this study indicate that Independent Commisioner, Audit Committee, Managerial Ownership, and CEO Ethnicity have a significantly positive impact on Audit Fees.